Chlorine isotope fractionation of the major chloromethane degradation processes in the environment - Keppler, Frank; Barnes, Jaime D.; Horst, Axel; Bahlmann, Enno; Luo, Jing; Nadalig, Thierry; Greule, Markus; Hartmann, Simon Christoph; Vuilleumier, Stéphane (Environmental science & technology letters, 2020)
Chloromethane (CH3Cl) is an important source of chlorine in the stratosphere, but detailed knowledge of the magnitude of its sources and sinks is missing. Here, we measured the stable chlorine isotope fractionation (εCl) associated with the major abiotic and biotic CH3Cl sinks in the environment, namely, CH3Cl degradation by hydroxyl (·OH) and chlorine (·Cl) radicals in the troposphere and by reference bacteria Methylorubrum extorquens CM4 and Leisingera methylohalidivorans MB2 from terrestrial and marine environments, respectively. No chlorine isotope fractionation was detected for reaction of CH3Cl with ·OH and ·Cl radicals, whereas a large chlorine isotope fractionation (εCl) of −10.9 ± 0.7‰ (n = 3) and −9.4 ± 0.9 (n = 3) was found for CH3Cl degradation by M. extorquens CM4 and L. methylohalidivorans MB2, respectively. The large difference in chlorine isotope fractionation observed between tropospheric and bacterial degradation of CH3Cl provides an effective isotopic tool to characterize and distinguish between major abiotic and biotic processes contributing to the CH3Cl sink in the environment. Our findings demonstrate the potential of emerging triple-element isotopic approaches including chlorine to carbon and hydrogen analysis for the assessment of global cycling of organochlorines.
Gesehen am 01.04.2020